2015
DOI: 10.1016/j.jcf.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor and sinonasal pathology in a cystic fibrosis patient with genotype deltaF508/S1215N

Abstract: In patients with Cystic Fibrosis and a type III mutation, ivacaftor (Kalydeco(®), Vertex) can increase the opening time of the CFTR channel and improve chloride transport. Research showed significant improvement of lung function and increase in weight following ivacaftor use. However, ivacaftor showed to have adverse events on the sinonasal system as well, such as upper respiratory tract infections, nasal congestion and headaches. This case report showed a positive effect of ivacaftor on the sinonasal patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…So far, it has not been possible to determine effects of novel therapies on inflammation and remodeling of the airway mucosa in patients with CF. Based on the present study results and considering ongoing developments in OCT technology with improved spatial resolution, our results suggest further development of OCT imaging as a potential minimal-invasive quantitative endpoint of mucosal alterations in CF clinical trials testing novel treatment modalities including systemic causal treatment with recently introduced CFTR modulators ivacaftor and lumacaftor [8,9,[18][19][20] or topical anti-inflammatory and antibiotic treatment with pulsed nasal nebulizers [7,21,22]. In this context, OCT imaging of the nasal mucosa was reproducible and easy to apply in the clinical setting.…”
Section: Discussionsupporting
confidence: 54%
“…So far, it has not been possible to determine effects of novel therapies on inflammation and remodeling of the airway mucosa in patients with CF. Based on the present study results and considering ongoing developments in OCT technology with improved spatial resolution, our results suggest further development of OCT imaging as a potential minimal-invasive quantitative endpoint of mucosal alterations in CF clinical trials testing novel treatment modalities including systemic causal treatment with recently introduced CFTR modulators ivacaftor and lumacaftor [8,9,[18][19][20] or topical anti-inflammatory and antibiotic treatment with pulsed nasal nebulizers [7,21,22]. In this context, OCT imaging of the nasal mucosa was reproducible and easy to apply in the clinical setting.…”
Section: Discussionsupporting
confidence: 54%
“…CFTR function, dichotomized to >1% or ≤1%, correlated with a history of surgical intervention for sinus disease. Our results are consistent with those of other studies, which have shown that improving CFTR function with small‐molecule modulators, such as ivacaftor, improves sinus symptoms and reverses sinus disease in patients with CF 33,34 …”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have documented both in vivo and in vitro effects following administration of ivacaftor. Several case reports have reported improvement in objective computed tomography (CT) findings in the sinuses of CF patients after treatment with ivacaftor . Chang et al .…”
Section: Discussionmentioning
confidence: 99%